ANALISIS TINGKAT LITERASI KEUANGAN MAHASISWA - Ria Herdiana (Pendidikan Ekonomi FPEB Universitas Pendidikan Indonesia, 2021)
This research is motivated by the need for student financial literacy to be able to live independently. The purpose of this study is to describe the level of student financial literacy and aspects of financial literacy used in this study include: aspects of basic knowledge of personal finance, savings and savings, insurance and investment. This research is a descriptive study based on a survey of research subjects. While the subjects of this research are students of the Economic Education study program, Faculty of Teacher Training and Education, Langlangbuana University for the 2019-2020 academic year, which consists of several semester levels and has obtained course achievements different according to the applicable curriculum. The data collection technique used in this study was using a questionnaire. The data analysis technique used in this research is descriptive qualitative analysis. The results of the study illustrate that the average level of financial literacy for students of Economics Education Faculty of Teacher Training and Education for the academic year 2019 – 2020, the level of financial literacy achieved by respondents from the average value for all aspects of financial literacy falls into the medium criteria. The lowest average level of financial literacy aspects is at aspects of savings and loans are included in the low category, while the highest average level of financial literacy is in the general knowledge aspect of personal finance which is included in the medium category.